IDENTIFICATION AND CHARACTERIZATION OF FEED PLANTS FOR Apis dorsata Binghami IN THE PINABETENGAN FOREST, MINAHASA - Feydina Tewu; Orbanus Naharia; Yermia Mokosuli (Indonesian Biodiversity Journal, 2023)
Apis Dorsata Binghami is a honey bee that is often found in the forest, which is conserved by the community, but there are also honey bees that are just left alone; the community preserves these honey bees because their honey can be traded and can also be used as medicine. This study aims to determine the plants that are a feed source for Apis Dorsata Binghami in the Pinabetengan Forest, Minahasa Regency. This research was conducted in June-August 2022. The data collected came from field survey data using descriptive methods and identified plant species with values of Reactive Density (KR), Relative Frequency (FR), Relative Dominance (DR), and Index Significant Value (INP). Plant diversity as a food source for Apis Dorsata Binghami has different types of plants based on their habitus or the characteristics of the plants themselves.